Neuroimaging - Marta Del-Ben, Cristina (IntechOpen, 2010)
Neuroimaging has become a crucial technique for Neurosciences. Different structural, functional and neurochemical methods, developed in recent decades, have allowed a systematic investigation on the role of neural substrates involved in functions performed by the central nervous system, whether normal or pathological. This book includes contributions from the general area of the neuroimaging to the understanding of normal functions and abnormalities of the central nervous system.